THE LEARNING MOTIVATION AND LEARNING ACHIEVEMENTS WITH INDIGENOUS SOCIOCULTURAL BACKGROUNDS - Marvi, Josafat; Bunau, Eusabinus; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to identify the indigenous students learning motivation and sociocultural backgrounds and its relationship into their learning achievements while enrolled in the education at English Education Study Program in Teacher Training and Education Faculty of Tanjungpura University academic year 2016/2017. Based on case study research method, the writer classified the indigenous students from Regular A and PPAPK class of 2016/2017 students who are still active at study process from the first semester and still consistent in learning until the beginning of the sixth semester in the year 2019. Only 7 students from Regular A and PPAPK class who remained in the sample of collecting process. Based on this two tools of research the result shows that the Indigenous Students are capable to reach high satisfactory of achievements which are supported by the internal factor and external factors. Each indigenous student has different internal and external factors in order to supports their learning process at college.                                               Keywords: Indigenous, Learning Motivation, Sociocultural Backgrounds, Learning Achievements